Hubungan Karakteristik dengan Tingkat Pengetahuan Keluarga Pasien terkait Beyond Use Date (BUD) Obat Sirup Kering - Atmi, Nur Azizah; Rhamdany, Muh. Wisda Praja; Putra, Made Sandi Pratama (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Most households in Indonesia keep a stock of medicines, but the public's knowledge of medicine storage remains low. The term BUD in drug storage is very important to know because BUD is related to the stability and quality of drugs. If drug storage is not appropriate, it can result in irrational drug use. This research aims to determine the relationship between characteristics and the patient's family's level of knowledge about the BUD of dry syrup at the Mataram City Regional Hospital. This research is a type of analytical observational research with a cross-sectional design that uses a valid (0.411-0.780) and a reliable (>0.06) questionnaire instrument. The respondents involved in this study were 60 guardians of patients who received dry syrup medication. The level of knowledge of the patient's guardians regarding BUD for dry syrup is dominated by the excellent category. The highest results of filling out the questionnaire were 56 people, with a correct answer of 76% - 100%. The bivariate analysis using chi-square shows that the characteristic that is related to the level of knowledge about BUD dry syrup medicine is the level of education (p=0.007). The domain of information sources supporting BUD for dry syrup medicine also relates to the respondents' knowledge level of BUD for dry syrup (p=0.000). This study concludes that only the characteristics of the level of education have a relationship with the level of knowledge of the patient's guardians regarding BUD dry syrup.